Neuroimaging of a minipig model of Huntington's disease: Feasibility of volumetric, diffusion-weighted and spectroscopic assessments - Schubert, Robin; Frank, Frauke; Nagelmann, Nina; Liebsch, Lennart; Schuldenzucker, Verena; Schramke, Sarah; Wirsig, Maike; Johnson, Hans; Kim, Eun Young; Ott, Stefanie; Hölzner, Eva; Demokritov, Sergej O; et al. (Journal of neuroscience methods, 2016)
BACKGROUND: As novel treatment approaches for Huntington's disease (HD) evolve, the use of transgenic (tg) large animal models has been considered for preclinical safety and efficacy assessments. It is hoped that large animal models may provide higher reliability in translating preclinical findings to humans, e.g., by using similar endpoints and biomarkers. NEW METHOD: We here investigated the feasibility to conduct MRI assessments in a recently developed tgHD model in the Libechov minipig. The model is characterized by high genetic homology to humans and a similar body mass and compartments. The minipig brain provides anatomical features that are attractive for imaging studies and could be used as endpoints for disease modifying preclinical studies similar to human HD. RESULTS: We demonstrate that complex MRI protocols can be successfully acquired with tgHD and wild type (wt) Libechov minipigs. We show that acquisition of anatomical images applicable for volumetric assessments is feasible and outline the development of a segmented MRI brain atlas. Similarly diffusion-weighted imaging (DWI) including fiber tractography is presented. We also demonstrate the feasibility to conduct in vivo metabolic assessments using MR spectroscopy. COMPARISON WITH EXISTING METHODS: In human HD, these MRI methods are already validated and used as reliable biomarker of disease progression even before the onset of a clinical motor phenotype. CONCLUSIONS: The results show that the minipig brain is well suited for MRI assessments in preclinical studies. We conclude that further characterization of phenotypical differences between tg and wt animals in sufficiently powered cross-sectional and longitudinal studies is warranted.
Keywords: Animals; Huntingtonova nemoc; Swine, Miniature; Magnetic Resonance Imaging; Female; Animals, Genetically Modified; Animal models; ženské pohlaví; Organ Size; Proton Magnetic Resonance Spectroscopy; neurozobrazování; miniaturní prasata; Preclinical research; magnetická rezonanční tomografie; prasata; mozek; velikost orgánu; modely nemocí na zvířatech; Brain; Huntington Disease; Swine; Disease Models, Animal; Brain atlas; MRI; zvířata; geneticky modifikovaná zvířata; Minipig; Neuroimaging; protonová magnetická rezonanční spektroskopie